Influence of Parental Involvement and School Environment on Pupils’ Academic Performance in The English Language - Usman Tunde Saadu (Universitas Pendidikan Indonesia (UPI), 2023)
This study examines the factors influencing academic performance, specifically in the context of English language proficiency, among students in Nigeria. The importance of English language proficiency in the Nigerian education system is highlighted, as it serves as the medium of instruction and the language of textbooks. Despite its significance, students' performance in written and spoken English is generally poor. The study emphasizes the role of various factors, including student-related factors (interest, motivation, study habits), teacher-related factors (teaching methods, experience, workload), and parental involvement in students' academic performance. Parental involvement is seen as crucial in shaping children's educational and environmental transformation, with active participation from parents positively impacting children's development, behavior, motivation, and academic performance. The study also recognizes the influence of the school environment on academic performance, emphasizing the need for a conducive learning environment with adequate resources and support services. The findings suggest that parental involvement and a supportive school environment contribute to improved academic performance. Overall, this study underscores the importance of addressing these factors to enhance students' English language proficiency and academic achievement in Nigeria.